2013
DOI: 10.1007/s00128-013-1149-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sediment Containing Coal Ash from the Kingston Ash Release on Embryo-Larval Development in the Fathead Minnow, Pimephales promelas (Rafinesque, 1820)

Abstract: The largest environmental release of coal ash in US history occurred in December 2008 with the failure of a retention structure at the Tennessee Valley Authority Kingston Fossil Fuel Plant in East Tennessee. A byproduct of coal-burning power plants, coal ash is enriched in metals and metalloids such as selenium and arsenic with known toxicity to fish embryonic and larval life stages. The early development of fish embryos and larvae during contact exposures to river bottom sediments containing up to 78 % coal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
0
8
2
Order By: Relevance
“…The results from this diverse range of studies overwhelmingly indicate that there was no toxicity of the Kingston fly ash in exposures to aquatic organisms inhabiting the overlying water column. Results from an extended ash elutriate study with fathead minnows (Stanley et al ) and an embryo‐larval development study with fathead minnows exposed directly to fly ash (Greeley et al ) further support these findings. These laboratory studies (Table ; Supplemental Data) and a study with amphipod, chironomid, and freshwater mussels exposed to fly ash (Wang et al ) support the finding that the potential toxicity to benthic species (both infaunal and epifaunal) is minimal to moderate, depending on the species and the percentage of ash present in the sediment.…”
Section: Discussionmentioning
confidence: 87%
“…The results from this diverse range of studies overwhelmingly indicate that there was no toxicity of the Kingston fly ash in exposures to aquatic organisms inhabiting the overlying water column. Results from an extended ash elutriate study with fathead minnows (Stanley et al ) and an embryo‐larval development study with fathead minnows exposed directly to fly ash (Greeley et al ) further support these findings. These laboratory studies (Table ; Supplemental Data) and a study with amphipod, chironomid, and freshwater mussels exposed to fly ash (Wang et al ) support the finding that the potential toxicity to benthic species (both infaunal and epifaunal) is minimal to moderate, depending on the species and the percentage of ash present in the sediment.…”
Section: Discussionmentioning
confidence: 87%
“…Measurement endpoints were mortality, hatching success, and developmental abnormalities. Greeley, Elmore et al (), Greeley, Elmore, McCracken, Sherrand (), and Greeley, Elmore, McCracken () provide more detail on the test methodology.…”
Section: Lines Of Evidencementioning
confidence: 99%
“…Because of the large volume of these data for several endpoints, this article presents only a summarized overview of study results, and does not include a detailed review of the actual data. Instead, additional details and summaries of the actual data can be found in the BERA (ARCADIS ), ancillary articles (Baker ; Greeley, Adams et al ; Greeley, Elmore et al ; Greeley, Elmore, McCracken, Sherrard ; Greeley, Elmore, McCracken ), and in other articles in this issue.…”
Section: Introductionmentioning
confidence: 99%
“…The spill at the Kingston Fossil Plant was one of the largest ash spill in US history (Ruhl et al 2009;Greeley et al 2014). Previous research investigating the effects of coal-ash-associated metals on aquatic organisms have focused primarily on areas receiving coal ash effluent (Reash et al 2006;Baumann and Gillespie 1986;Lohner et al 2001) and not from an environmental spill, as was the case in this study.…”
Section: Discussionmentioning
confidence: 91%
“…Otter et al (2012) showed elevated concentrations of arsenic and selenium in various tissues of multiple fish species at ash-associated sites compared to reference sites. Laboratory experiments showed elevated concentrations of arsenic, selenium, and mercury in sediment samples, but no effects on larval or juvenile fathead minnows (Pimephales promelas) when exposed to ash-amended sediment or elutriates (Stanley et al 2013;Greeley et al 2014). When the current body of research on the Kingston spill is viewed collectively, a couple of major observations can be made: (1) The major contaminants of concern appear to be metals, such as arsenic and selenium, and (2) metals associated with ash appear to be largely sediment-bound.…”
Section: Discussionmentioning
confidence: 99%